Analysis of the Influence of Religiosity, Ethical Leadership, and Opportunity to Achieve on Loyalty in the Airline Industry - Hernawan, Moch Arif; Lubis, Fatimah Malini; Usulu, Elvira M.; Andriani, Hertya; Nurdiani, Tanti Widia; Violin, Vivid (Yayasan Gema Bina Nusantara, 2025)
This study aims to analyze the influence of religiosity, ethical leadership, and achievement opportunities on employee loyalty in the airline industry in Indonesia. Employee loyalty is a crucial element in maintaining an organization’s competitive advantage, particularly in the service industry, which heavily relies on the quality of human resources. This research adopts a quantitative approach by distributing questionnaires to 200 employees from various divisions across three national airlines. The religiosity variable was measured through the dimensions of belief, worship, and morality; ethical leadership was assessed through justice, integrity, and role-modeling; while achievement opportunity was evaluated based on perceptions of self-development opportunities and recognition. The data analysis technique used was Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that religiosity and ethical leadership have a positive and significant effect on employee loyalty. Meanwhile, achievement opportunity also has a significant effect, although its influence becomes stronger when mediated by job satisfaction. These findings suggest that organizations that support employees’ religious values, implement ethical leadership, and provide room for career achievement are more likely to foster high levels of employee loyalty.